Contribuição à paleoecologia da Amazônia Meridional na planície de inundação do Rio Teles Pires, do norte do Estado do Mato Grosso - Paixão, Jesus da Silva (Universidade Federal de São Carlos, 2010)
Records of isotopic and elemental carbon and nitrogen and pollen in lake sediments and soils have been used for studies of Quaternary paleoecology worldwide, including in the Amazon at specific sites, such as the region of Carajas, Lake Pata and Region Porto Velho in Rondonia state making it necessary to register in the central southern region. We collected two cores in the Lagoa Jabuti site and a core on the Site Três Coqueiros in the floodplain of the Teles Pires river in northern Mato Grosso state. The cores were analyzed for elemental and isotopic nitrogen and carbon (% C, % N, 13C, 15N and C/N), and palynology and radiometric dating by 14C via AMS. Was also used samples of Quaternary megafauna and elements of material culture. From the analysis carried out it appears that southern Amazon in the Mato Grosso there were no significant ecological changes during the study period, which is around 5,500 years B.P., except for the registration of a relatively sharp change in carbon isotope values for about 2,700 years BP. The pollen analysis of the sediment of Jabuti showed the predominance of elements on forest herb/fern coinciding with data from botanical surveys conducted in the area in which stand families Fabaceae, Arecaceae, Euphorbiaceae, Malvaceae, Combretaceae, Melastomataceae, Annonaceae, among the trees; Cyperaceae , Asteraceae, Chenopodiaceae, Poaceae, Achantaceae and Amaranthaceae between herbs and Polygonaceae, Cyatheaceae and Asplenium among the ferns. The megafauna considered in the paper presented by ESR beyond the age covered by the project and analyzed the material culture (ceramics) revealed that from the earliest moments of occupation (about 1,300 years BP) the ecological conditions of the region have not changed, although they have been registered large gaps in regional occupation that can be interpreted as a crisis in the supply of natural resources necessary for survival in the region.
Keywords: Paleoecologia; Geologia ambiental; Isótopos; Quaternário; Southern Amazon; Paleoecology; Quaternary; Isotopic Composition; Palynology; Megafauna; CIENCIAS BIOLOGICAS::ECOLOGIA